Rancang Bangun Alat Transfer Data Teks Nirkabel Bawah Air Berbasis Mikrokontroler - Erlin Yunus Duha; Joko Saputro; Sharyanto Sharyanto (FIKOM Universitas Bung Karno, 2022)
Communication is a very important factor to avoid misunderstanding, with communication it will be easy to understand what is meant between the object of introduction and the recipient of information. However, communication is still an obstacle for those who carry out underwater activities such as diving. Many ordinary divers do not understand the diver's signal code which will be a problem because of the difficulty in communicating if something happens that requires them to carry out information sharing activities underwater. Innovation is needed to be implemented, namely research that is able to facilitate divers to communicate underwater the same as using diver sign language. The purpose of this research is to design a wireless data transfer tool that can be used underwater by utilizing the Arduino microcontroller control board as a data processing component supported by an infrared sensor as a transmitting medium which aims to capture infrared light waves as a wireless communication medium. The marker components such as LEDs and LCDs indicate and display information from the processing results when data is successfully received and sent. The power distribution uses low voltage currents to carry out the performance of wireless data transfers underwater with the results of safe test criteria while the device is working in water.